SITVITBovis—a publicly available database and mapping tool to get an improved overview of animal and human cases caused by Mycobacterium bovis. (13th January 2022) - Couvin, David; Cervera-Marzal, Iñaki; David, Audrey; Reynaud, Yann; Rastogi, Nalin
Abstract: Limited data are available for bovine tuberculosis and the infections it can cause in humans and other mammals. We therefore constructed a publicly accessible SITVITBovis database that incorporates genotyping and epidemiological data on Mycobacterium bovis . It also includes limited data on Mycobacterium caprae (previously synonymous with the name M. bovis subsp. Caprae) that can infect both animals and humans. SITVITBovis incorporates data on 25, 741 isolates corresponding to 60 countries of origin (75 countries of isolation). It reports a total of 1000 spoligotype patterns: 537 spoligotype international types (SITs, containing 25 278 clinical isolates) and 463 orphan patterns, allowing a wide overview of the geographic distribution of various phylogenetical sublineages ( BOV _1, BOV _2, BOV _3 and BOV _4- CAPRAE ). The SIT identifiers of the SITVITBovis were compared to the SB numbers of the Mbovis.org database to facilitate crosscheck among databases. Note that SITVITBovis also contains limited information on mycobacterial interspersed repetitive units-variable number of tandem repeats when available. Significant differences were observed when comparing age/gender of human isolates as well as various hosts. The database includes information on the regions where a strain was isolated as well as hosts involved, making it possible to see geographic trends. SITVITBovis is publicly accessible at: http://www.pasteur-guadeloupe.fr:8081/SITVIT_Bovis . Finally, a future second version is currently in progress to allow query of associated whole-genome sequencing data. Database URLhttp://www.pasteur-guadeloupe.fr:8081/SITVIT_Bovis